2005
DOI: 10.1021/ma047764+
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and Inductive Thickenings of Lamellar Crystal Monolayers of Low Molecular Weight PEO Fractions on Surface of Solid Substrates

Abstract: Crystalline macromolecules form folded-chain lamellar and metastable crystals. Annealing at a temperature below melting point results in a thickening of the metastable crystals to construct more stable ones. Such a process was visualized by AFM equipped with a hot stage in monolayers of poly(ethylene oxide) lamellar crystals on a silicon wafer surface. Our observations show that the monolayers can be thickened in a stepwise manner during stepwise heating to temperatures below the melting point. Our analyses sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…Prior to the crystallization at 85°C, the cast films used for the morphology observation in this work was heated up to 140°C, which is above the equilibrium melting temperatures of it-PB1 tetragonal and trigonal crystals. The crystals formed in the solution casting process became completely melted in the heating process before the crystallization at 85°C and the inductive thickening as reported by Zhai et al [29] does not participate in the crystal growth at 85°C. It was demonstrated by Fu et al with in-situ small angle X-ray scattering experiments of melt it-PB1 crystallization process that it-PB1 tetragonal crystals do not present spontaneous thickening during the isothermal crystallization.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Prior to the crystallization at 85°C, the cast films used for the morphology observation in this work was heated up to 140°C, which is above the equilibrium melting temperatures of it-PB1 tetragonal and trigonal crystals. The crystals formed in the solution casting process became completely melted in the heating process before the crystallization at 85°C and the inductive thickening as reported by Zhai et al [29] does not participate in the crystal growth at 85°C. It was demonstrated by Fu et al with in-situ small angle X-ray scattering experiments of melt it-PB1 crystallization process that it-PB1 tetragonal crystals do not present spontaneous thickening during the isothermal crystallization.…”
Section: Discussionsupporting
confidence: 50%
“…At high supercooling conditions, the heat or mass diffusion field can play a key role in controlling the crystallization kinetics and crystal morphology. Zhai et al discovered temperature-independent crystallization patterns and morphologies in thin monolayer films of low molecular weight poly(ethylene oxide) (PEO) [29]. They demonstrated by in-situ atomic force microscopy observations that a competition exists between the monolayered lamellar crystals with different thicknesses in very thin films.…”
Section: Discussionmentioning
confidence: 99%
“…It is argued that the sliding motion is the main mechanism of causing the ST and 1 st -IT thickening processes, while the 2 nd -IT process is associated with the meltingrecrystallization mechanism. [34] Relatively speaking, the sliding motion may be easier, so takes place during the low temperature range of the entire thickening process. The melting-recrystallization mechanism contains at least three courses: the melting of thin crystals, the diffusion of melted molecules to thick crystals, and the recrystallization into thick crystals.…”
Section: Resultsmentioning
confidence: 99%
“…[10,13,[17][18][19][20][22][23][24]26] The meltingrecrystallization mechanism emphasizes the melting of thin lamellae and the recrystallization of melted molecules to form thick lamellae. [8,11,20,21,26] In our previous study [34] we have demonstrated a quantized thickening process of a crystal monolayer of PEO with M n ¼ 5 000 g Á mol À1 on the surface of a silicon wafer when the samples were heated from room temperature to an annealing temperature. Our in-situ AFM observations have demonstrated that the thickening could be divided into spontaneous and inductive processes.…”
Section: Full Papermentioning
confidence: 94%
See 1 more Smart Citation